2016
DOI: 10.1021/jacs.5b12081
|View full text |Cite
|
Sign up to set email alerts
|

One Photocatalyst, n Activation Modes Strategy for Cascade Catalysis: Emulating Coumarin Biosynthesis with (−)-Riboflavin

Abstract: Generating molecular complexity using a single catalyst, where the requisite activation modes are sequentially exploited as the reaction proceeds, is an attractive guiding principle in synthesis. This requires that each substrate transposition exposes a catalyst activation mode (AM) to which all preceding or future intermediates are resistant. While this concept is exemplified by MacMillan's beautiful merger of enamine and iminium ion activation, examples in other fields of contemporary catalysis remain elusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
130
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 237 publications
(140 citation statements)
references
References 78 publications
4
130
0
6
Order By: Relevance
“…[1][2][3] Generating both E-a nd Z-substrate isomers is,h owever,o ften complicated by mechanistic and/or thermodynamic constraints, [4] requiring independent synthesis routes to be developed to prepare both substrates. [4,5,7,8] Predicated on selective energy transfer from an excited-state photosensitiser to the starting material, [4,5,9] this platform ensures that only the E-geometric isomer is activated. In the case of styrenyl systems that contain an embedded chromophore,e nergy transfer catalysis offers ap ractical activation method to achieve efficient geometrical E!Z isomerisation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Generating both E-a nd Z-substrate isomers is,h owever,o ften complicated by mechanistic and/or thermodynamic constraints, [4] requiring independent synthesis routes to be developed to prepare both substrates. [4,5,7,8] Predicated on selective energy transfer from an excited-state photosensitiser to the starting material, [4,5,9] this platform ensures that only the E-geometric isomer is activated. In the case of styrenyl systems that contain an embedded chromophore,e nergy transfer catalysis offers ap ractical activation method to achieve efficient geometrical E!Z isomerisation.…”
Section: Introductionmentioning
confidence: 99%
“…Coumarins, the important structural motifs in natural products and bioactive compounds, exhibiting broad biological activities, have been the targets for many organic syntheses [32][33][34]. Among many successful methods developed over the years, cyclization of ortho-hydroxycinnamates via double-bond isomerization was the one which was generally convenient from easily obtained starting material and afforded the coumarins in very good yields.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was shown that the oxidation power of RFTA can be increased by coordination to scandium triflate [14]. Recently, the E / Z -isomerization of olefins with riboflavin as catalyst was reported [15], which was also used for cyclization to form coumarins [16]. …”
Section: Resultsmentioning
confidence: 99%